Sams teach yourself Gmail in 10 minutes - Miller, Michael, 1958- (Sams, 2015)
Sams Teach Yourself Gmail in 10 Minutes, Second Edition, gives you straightforward, practical answers when you need fast results. Work through its 10-minute lessons to make the most of the world's most powerful and popular email system! This book will show you how to send and receive email from any web browser or smartphone using Gmail. You'll learn how to send pictures and other file attachments, add a signature to your outgoing messages, and customize Gmail for your own personal use. You'll even learn how to create and organize your Gmail contacts!